BATAKO STYROFOAM KOMPOSIT MORTAR SEMEN - Wancik, Ahmad; Satyarno, Iman; Tjokrodimuljo, Kardiyono (Civil Engineering Forum Teknik Sipil, 2008)
Research in construction material by exploiting styrofoam as lightweight concrete, gives result that a construction material will have a lighter weight if it is mixed with styrofoam, and achieve a lower strength. This research were try to improve the strength of styrofoam concrete block composite by giving cement mortar mixture as an outer layer. The specimen of concrete block composite will be made with concrete method of preplaced concrete, where initially by putting down the concrete block composite with styrofoam into a mold according to various thickness of outer layer required, and mortar mixture as outer layer around it. It was found that the compressive strength of concrete block with various outer layer thickness of 5, 10, and 15 mm without cord net were reached at 2.52 MPa, 5.44 MPa and 7.49 Mpa respectively with weight per piece were 7.60 kgs, 9.06 kgs, and 10.23 kgs. The compressive strength of concrete block with cord net size 100 mmÂ² were reached 3.27 MPa, 5.75 MPa and 8.58 MPa respectively with same various outer layer thickness and weigh per piece reached at 8.06 kgs, 9.15 kgs, and 10.28 kgs. Water absorption of outer layer were achieved 2,01 % and 7,06 % for soaking during 10 minutes and 24 hours respectively. Generally, the composite styrofoam concrete block with cement mortar outer layer thickness of 5 mm, 10 mm and 15 mm has meet a clauses of SNI requirements to solid concrete block for concrete block quality IV, quality III and quality II.